Pengembangan Antarmuka Aplikasi Monitoring Santri Pondok Pesantren Al-Azhar Berbasis Web Dengan Metode User Centered Design - Syah, Aditya Lukman; Umam, Khoirul; Haq, Endi Sailul; Suardinata, I Wayan; Suwardiyanto, Devit (Jurnal Informatika dan Komputer, 2025)
Abstract One of the Islamic boarding schools located in Banyuwangi is the Al-Azhar Modern Islamic Boarding School, which is located in Muncar District. At the Al-Azhar Islamic Boarding School, information regarding the development of students is only provided during the distribution of report cards at the end of the semester and only contains information regarding academic development. So when a student's guardian wants to know about a child's development, they have to visit the Islamic boarding school directly. Visits are limited to two times a month. This causes parents to be less able to monitor their child's development effectively and can lead to miscommunication. Given this problem, a student-based monitoring application is needed web as a medium for conveying information regarding the development of students with the main features, namely violations, absenteeism, assessments, achievements. In designing the interface, researchers use methods User Centered Design (UCD), this method was chosen because it involves the user in the design process to create an interface design that suits the user's needs. Researchers carried out tests using the method System Usability Scale (SUS) to assess the level of application usability for 30 respondents, namely student administrators and guardians with the final SUS result of each feature getting a score of 75.7 converted into Grade B. It can be concluded that the interface development created is in accordance with the user's needs and desires.